Investment overseas : why China? - Ng, Cheng Hann (2015)
To maintain economic growth in the long run, direct foreign investment (DFI) is necessary for Singapore. The Senior Minister of Singapore, Lee Kuan Yew, at the beginning of January 1993, strongly encouraged Singaporeans to venture out of the protected shell of Singapore to the neighbouring countries, namely China, India, Indonesia and Vietnam. This would help the government achieve its aim of building an external wing in Singapore's economy. The opening up of the economies in several Asian countries offers Singapore many opportunities for investment. One of these countries is China. China, being the most populous and the third largest country in the world, is a land full of opportunities. Its vast domestic market, large pool of manpower and large available land resources are very attractive to any foreign investors. Hence, Singaporeans should consider venturing into China and reap the returns from their investments there.